Adverse effects of the pesticide chlorpyrifos on the physiology of a damselfly only occur at the cold and hot extremes of a temperature gradient. (1st June 2023) - Verheyen, Julie; Cuypers, Kiani; Stoks, Robby
Abstract: Ecotoxicological studies considerably improved realism by assessing the toxicity of pollutants at different temperatures. Nevertheless, they may miss key interaction patterns between pollutants and temperature by typically considering only part of the natural thermal gradient experienced by species and ignoring daily temperature fluctuations (DTF). We therefore tested in a common garden laboratory experiment the effects of the pesticide chlorpyrifos across a range of mean temperatures and DTF on physiological traits (related to oxidative stress and bioenergetics) in low- and high-latitude populations of Ischnura elegans damselfly larvae. As expected, the impact of chlorpyrifos varied along the wide range of mean temperatures (12–34 °C). None of the physiological traits (except the superoxide anion levels) were affected by chlorpyrifos at the intermediate mean temperatures (20–24 °C). Instead, most of them were negatively affected by chlorpyrifos (reduced activity levels of the antioxidant defense enzymes superoxide dismutase [SOD], catalase [CAT] and peroxidase [PER], and a reduced energy budget) at the very high (≥28 °C) or extreme high temperatures (≥32 °C), and to lesser extent at the lower mean temperatures (≤16 °C). Notably, at the lower mean temperatures the negative impact of chlorpyrifos was often only present or stronger under DTF. Although the chlorpyrifos effects on the physiological traits greatly depended on the experimentally imposed thermal gradient, patterns were mainly consistent across the natural latitude-associated thermal gradient, indicating the generality of our results. The thermal patterns in chlorpyrifos-induced physiological responses contributed to the observed toxicity patterns in life history (reduced survival and growth at low and high mean temperatures). Taken together, our results underscore the importance of evaluating pesticide toxicity along a temperature gradient and of taking a mechanistic approach with a focus on physiology, to improve our understanding of the combined effects of pollutants and temperature in natural populations. Graphical abstract: Image 1 Highlights: Chlorpyrifos effects on physiology varied along a wide range of temperatures. Chlorpyrifos had adverse effects at low and especially at high mean temperatures. However, at intermediate temperatures, chlorpyrifos did not affect the physiology. Patterns in physiological traits were strongly correlated with life history traits.